Influência da dexametasona e levamisol no recrutamento de macrófagos, formação de células gigantes e parâmetros hematológicos no peixe tropical Piaractus mesopotamicus - Petrillo, Thalita R. [UNESP]; Claudiano, Gustavo da Silva [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Manrique, Wilson Gomez [UNESP]; de Castro, Marcelo Pardi [UNESP]; Belo, Marco Antonio de Andrade [UNESP]; de Moraes, Julieta R. Engrácia [UNESP]; de Moraes, Flávio Ruas [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
The aim of this study was to evaluate the effect of parenteral administration of dexamethasone and levamisole on the accumulation of macrophages and formation of giant cells in chronic inflammation by foreign body and blood parameters in pacu (Piaractus mesopotamicus). It was used 50 mg/kg of levamisole and 2.0 mg/kg of dexamethasone and the combination of both drugs. Coverslips were implanted under the skin. After 2, 7, and 15 days postimplantation (DPI), fish were anesthetized for removal of coverslips and the number of macrophages and giant cells were count. It was also collected blood from the caudal vessel to evaluate: red blood cell count, hematocrit, hemoglobin concentration, leukocytes count, thrombocytes count, MCV, and MCHC. We observed that dexamethasone affects negatively the formation of giant cells in the chronic inflammation for foreign body. Levamisole, despite being immunostimulatory in several species, showed limited action. However, it was enough to counteract the effect of dexamethasone; the association of the drugs did not interfere significantly in erythrocyte and leukocyte number in most of the treatments and times studied. In dexamethasone group there was a reduction in the number of erythrocytes and hemoglobin associated with increased mean corpuscular volume, suggesting slight macrocytic anemia. At 15 DPI, most groups showed the recovery of hematologic response. As in mammals, dexamethasone affects negatively the inflammatory response. Levamisole showed little effect by itself. However, in some parameters the association of both drugs causes similar response to control and naïve groups, showing the antagonistic effect of these drugs.
Influence of dexamethasone and levamisole on macrophage recruitment, giant cell formation and blood parameters in the tropical fish Piaractus mesopotamicus
Keywords: Coverslips; Glucocorticoid; Inflammation; Pacu